A Review of Indonesian Pre-Service Teacher Certification Policy from the Point of View of the Philosophy of Vocational Education - Estriyanto, Yuyun (Sebelas Maret University, 2016)
Teacher certification was a consequence of Indonesian teacher professional acknowledgement. In the first step, the certification was conducted for the existing teachers. It was started in 2006 and planned to be completed in 2015. Starting from 2016 pre-service teacher certificate, which should be obtained from the pre-service teacher professional education program, is a requirement for new teacher recruitment. The guideline of the program was regulated under the provision of Indonesian Minister of Education and Culture No. 87 2013. Based on this regulation, the participant prior education background could be: (a) educational bachelor degree in accordance with professional education program taken; (b) educational bachelor degree allied with professional education program taken; (c) non-educational bachelor/D-IV in accordance with professional education program taken; (d) non-educational bachelor/D-IV allied with professional education program taken; and (e) bachelor degree in psychology for pre and elementary school. From the point of view of the vocational education philosophy, the regulation was not completely appropriate. Vocational education will be effective when the instructor has had successful experience in the application of skills and knowledge to the operations and processes he undertakes to teach. From the deep review of philosophical aspect, characteristic of all prior learning of pre-service teacher professional education types, and vocational teacher theory found that hands-on skill and experience is a high priority requirement for vocational teacher. This type of competence was not owned by all participants who came from any type of prior education. Based on the program structure, it could be concluded that matriculation is the only part of the program where hands-on skill and experience could be delivered.